'It was made to appear to them so': the crucifixion, Jews and Sasanian war propaganda in the Qur'ān. Issue 3 (3rd July 2021) - Cole, Juan
ABSTRACT: The quranic sūra The Women 4:157-58 says that Jews claimed to have killed and crucified Christ but denies that they did so. Rather, the verse says, 'it was made to appear to them so.' For centuries, controversy has swirled around these verses, as most Muslims took them to deny that Christ was crucified. If we place them in the historical context of the Roman-Sasanian war of the early seventh century, it is clear that the allegations denied in this Qurʾān passage resemble reported taunts of Sasanian war propagandists seeking to demoralize their Christian foes. These verses about the crucifixion are preceded in The Women 4:153-156 by accusations leveled at Jews of having been unfaithful to their own covenant and of having killed prophets that came to them. It is shown that these charges against the Jews are closely based on a biblical passage, the penitential prayer of Ezra in Nehemiah 9.